2012
DOI: 10.3892/mmr.2012.926
|View full text |Cite
|
Sign up to set email alerts
|

Association between the C3435T single-nucleotide polymorphism of multidrug resistance 1 gene and risk of gastric cancer

Abstract: The multidrug resistance 1 (MDR1) gene encodes P-glycoprotein, which confers resistance to antineoplastic drugs, but also affects the kinetic disposition of certain drugs and carcinogens. The C3435T polymorphism of the MDR1 gene may influence the transport and excretion of carcinogens, increasing the risk of cancer. The aim of this study was to evaluate the association between this polymorphism and the risk of gastric cancer (GC). Ninety-eight patients with non-cardia GC and 203 healthy subjects participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several studies have investigated the relationship between ABCB1 polymorphisms and H. pylori infection [13][14][15]. For instance, two Australian studies showed a strong association between them [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the relationship between ABCB1 polymorphisms and H. pylori infection [13][14][15]. For instance, two Australian studies showed a strong association between them [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these polymorphisms may have a direct effect on ABCB1 gene expression and function of the ABCB1 protein (Fromm et al, 2002;Ambudkar et al, 2006Salama et al, 2006;Dean, 2009). Nevertheless, in previous studies conducted by our group (Oliveira et al, 2012;Wu et al, 2014), described a lack of association of the MDR1 C3435T polymorphism with susceptibility to GC. Differently, in another field study by Ren et al (2012), suggested that the MDR1 gene polymorphism was strongly associated with increased susceptibility to hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 79%